A model of inflation for Bangladesh - Begum, Nazma (The Philippine Review of Business and Economics, 1991)
The study formulates a model of inflation for Bangladesh using a detailed approach which concentrates both on aggregate supply and demand. The final model consisting of nine semi-reduced form equations is empirically tested. The empirical test of the inflation equation of the model shows that the significant variables for inflation are agricultural and import bottlenecks, government expenditure, wage rate, bank credit and expected inflation. The signs of the coefficients of agricultural bottlenecks, rate of interest and credit show the dominance of the supply-side cost-push effect while the signs of the coefficients of import bottlenecks, government expenditure, wage and expected inflation show the dominance of the demand side effect. The policy shocks applied to the model reveals that devaluation reduces output and investment. Reduction in bank credit reduces output, investment, and export while increasing prices. A simultaneous increase in exchange rate and decrease in bank credit reduces output, export and investment, and increase price inflation or in effect leads to stagflation.